Neddylation inhibitor MLN4924 has anti‐HBV activity via modulating the ERK‐HNF1α‐C/EBPα‐HNF4α axis. Issue 2 (2nd December 2020) - Xie, Mingjie; Guo, Huiting; Lou, Guohua; Yao, Jiping; Liu, Yanning; Sun, Yi; Yang, Zhenggang; Zheng, Min
Abstract: Hepatitis B virus (HBV) infection is a major public health problem. The high levels of HBV DNA and HBsAg are positively associated with the development of secondary liver diseases, including hepatocellular carcinoma (HCC). Current treatment with nucleos(t)ide analogues mainly reduces viral DNA, but has minimal, if any, inhibitory effect on the viral antigen. Although IFN reduces both HBV DNA and HBsAg, the serious associated side effects limit its use in clinic. Thus, there is an urgent demanding for novel anti‐HBV therapy. In our study, viral parameters were determined in the supernatant of HepG2.2.15 cells, HBV‐expressing Huh7 and HepG2 cells which transfected with HBV plasmids and in the serum of HBV mouse models with hydrodynamic injection of pAAV‐HBV1.2 plasmid. RT‐qPCR and Southern blot were performed to detect 35kb mRNA and cccDNA. RT‐qPCR, Luciferase assay and Western blot were used to determine anti‐HBV effects of MLN4924 and the underlying mechanisms. We found that treatment with MLN4924, the first‐in‐class neddylation inhibitor currently in several phase II clinical trials for anti‐cancer application, effectively suppressed production of HBV DNA, HBsAg, 3.5kb HBV RNA as well as cccDNA. Mechanistically, MLN4924 blocks cullin neddylation and activates ERK to suppress the expression of several transcription factors required for HBV replication, including HNF1α, C/EBPα and HNF4α, leading to an effective blockage in the production of cccDNA and HBV antigen. Our study revealed that neddylation inhibitor MLN4924 has impressive anti‐HBV activity by inhibiting HBV replication, thus providing sound rationale for future MLN4924 clinical trial as a novel anti‐HBV therapy.